A standardized system of training-intensity guidelines for track and field and cross country coaches - Belcher, C. P.; Pemberton, C. L. (Journal of Coaching Education, 2013)
A training program designed to optimize athletes` performance abilities cannot be practically planned or implemented without a valid and reliable indication of training intensity and its effect on the physiological mechanisms of the human body. The objectives of this paper are to (a) review training-intensity guidelines developed for coaches, inclusive of the associated physiologic metrics validated in a field study; (b) describe a seasonal application of the guidelines for coaches; and (c) share supporting commentary from coaches interviewed in the field study. A standardized system of training-intensity guidelines for the sports of track and field/cross country was field tested. The system was modeled after the standardized system of training-intensity guidelines used by USA Swimming. Track and field and cross country coaches were asked to comment on the perceived utility of the standardized training-intensity guidelines. Results of the field study show that coaches uniformly confirmed the utility and applicability of the training-intensity guidelines.